The Impact of Halloysite on the Thermo-Mechanical Properties of Polymer Composites - Gaaz, Tayser Sumer (Molecules, 2017)
Nanotubular clay minerals, composed of aluminosilicate naturally structured in layers known as halloysite nanotubes (HNTs), have a significant reinforcing impact on polymer matrixes. HNTs have broad applications in biomedical applications, the medicine sector, implant alloys with corrosion protection and manipulated transportation of medicines. In polymer engineering, different research studies utilize HNTs that exhibit a beneficial enhancement in the properties of polymer-based nanocomposites. The dispersion of HNTs is improved as a result of pre-treating HNTs with acids. The HNTs’ percentage additive up to 7% shows the highest improvement of tensile strength. The degradation of the polymer can be also significantly improved by doping a low percentage of HNTs. Both the mechanical and thermal properties of polymers were remarkably improved when mixed with HNTs. The effects of HNTs on the mechanical and thermal properties of polymers, such as ultimate strength, elastic modulus, impact strength and thermal stability, are emphasized in this study.